A review of the open laparoscopic Hasson technique and retrieval of adnexal specimen via umbilicus. (19th May 2017) - Wong, L. F. A.; Anglim, B.; Wahab, N. A.; Gleeson, N.
Abstract: Laparoscopic entry techniques vary amongst surgeons and gynaecologists, with gynaecologists favouring Veress needle entry. Recent RCOG/BSGE recommendations have recommended retrieval of ovarian masses via the umbilical port with resultant less postoperative pain and a faster retrieval time than with retrieval through lateral ports of the same size. This is a prospective observational study reviewing the Hasson entry technique and the introduction of retrieval of specimens via the umbilicus in patients scheduled for a laparoscopy procedure at our day surgery unit. We found no immediate or major surgical complications and all specimens were successfully retrieved through the umbilicus. Pain scores were low. We recommend the technique for extirpative gynaecological surgery. Impact Statement: This study confirms that conversion from the closed Veress to the open Hasson technique is achievable in a university hospital setting. Operator confidence during the learning phase is enhanced by the use of ultrasound to locate and measure the depth of the umbilical ligament. Retrieval of benign adnexal specimens through the umbilicus was very satisfactory.